2015
DOI: 10.1111/hsc.12242
|View full text |Cite
|
Sign up to set email alerts
|

Locality, loneliness and lifestyle: a qualitative study of factors influencing women's health perceptions

Abstract: Locality, loneliness and lifestyle: a qualitative study of factors influencing women's health perceptions. AbstractThe contribution of women to the achievement of global public health targets cannot be underestimated. It is well evidenced that within families, women are a key influence on the health and wellbeing of their children and partners. However geographical differences in women's health inequalities persist and research focusing specifically on women's perceptions of locality factors influencing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Of the 27 studies on emotional loneliness, seven studies explored emotional loneliness as a consequence of relational issues [132,136,138,142,148,153,155,157], further supporting the idea that social and emotional loneliness are interconnected. Four of these identified that complex family dynamics including responsibility for childcare, older children leaving home, and bereavement (for mothers) [132]; poor childhood attachment (to fathers), and weak sibling relationships [153]; being placed in a care home [148]; and loss of intimate partner relationships [136,155]. These all resulted in the deeply emotional character of loneliness connected to low mood, a lack of sense of purpose and feelings of suffering, family abandonment, and pervasive worry.…”
Section: Emotional Lonelinessmentioning
confidence: 80%
See 1 more Smart Citation
“…Of the 27 studies on emotional loneliness, seven studies explored emotional loneliness as a consequence of relational issues [132,136,138,142,148,153,155,157], further supporting the idea that social and emotional loneliness are interconnected. Four of these identified that complex family dynamics including responsibility for childcare, older children leaving home, and bereavement (for mothers) [132]; poor childhood attachment (to fathers), and weak sibling relationships [153]; being placed in a care home [148]; and loss of intimate partner relationships [136,155]. These all resulted in the deeply emotional character of loneliness connected to low mood, a lack of sense of purpose and feelings of suffering, family abandonment, and pervasive worry.…”
Section: Emotional Lonelinessmentioning
confidence: 80%
“…These all resulted in the deeply emotional character of loneliness connected to low mood, a lack of sense of purpose and feelings of suffering, family abandonment, and pervasive worry. Such negative consequences of emotional loneliness could be further entrenched by disadvantaged living conditions, such as low income and limited access to spaces/places with good amenities [132]. This evidence points to the significance of high quality and meaningful relationships and an understanding of the role of place/space in countering social and emotional loneliness.…”
Section: Emotional Lonelinessmentioning
confidence: 88%
“…Several independent variables were explored as being factors that were potentially related to loneliness from an ecological systems model [ 14 ]. These variables were selected based on literature reviews of previous studies [ 4 – 9 , 15 21 ] and 3 focused group interviews with 41 professionals or community volunteers, and 31 one-to-one interviews with mothers raising children less than 3 years of age.…”
Section: Study Variablesmentioning
confidence: 99%
“…Loneliness influences the mental health of adult women worldwide, and women constitute a higher risk population than men [ 3 ]. Particularly, mothers staying at home with young children have been identified as a high-risk population for loneliness [ 4 , 5 ]. One previous longitudinal study showed the prevalence of loneliness among mothers was between 34 and 38% [ 6 ], and it was associated with both mothers’ depression and children’s adjustment [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation